2007
DOI: 10.1186/1475-2840-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the individual components of the metabolic syndrome and their different combinations on the prevalence of atherosclerotic vascular disease in type 2 diabetes: the Diabetes in Germany (DIG) study

Abstract: Background: One of the major controversies surrounding the metabolic syndrome (MetS) in type 2 diabetes is whether its single components act synergistically as risk factors for atherosclerotic vascular disease (AVD). We aimed to answer this by evaluating the relationship, and its various combinations to AVD in comparison to single traits in a population-based study with type 2 diabetes in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
12

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 16 publications
8
56
1
12
Order By: Relevance
“…No association was found between stroke and the presence of MS per se at baseline, or the cumulative number of MS components. The relatively low prevalence of MS and hypertension observed in our diabetic population compared to other studies 5 could be attributed to the relatively low mean age and the adoption of a Mediterranean diet 6 by Greek patients.…”
Section: Discussioncontrasting
confidence: 45%
“…No association was found between stroke and the presence of MS per se at baseline, or the cumulative number of MS components. The relatively low prevalence of MS and hypertension observed in our diabetic population compared to other studies 5 could be attributed to the relatively low mean age and the adoption of a Mediterranean diet 6 by Greek patients.…”
Section: Discussioncontrasting
confidence: 45%
“…We found that obesity and arterial hypertension were each individually associated with a modestly increased risk of serious liver disease; however, the risk was highest in the presence of diabetes. In other studies, the combination of diabetes and the metabolic syndrome posed a higher risk for stroke 14 and myocardial infarction 15 than either condition alone. For a variety of reasons, the same phenomenon may be true for liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, Hanefeld and coworkers showed that in people with type 2 diabetes, the cluster of diabetes with hypertension seemed more strongly associated with the concurrence of cardiovascular events than other clusters of MetSyn. 29 MetSyn comprises heterogeneous clusters of individual components or traits. Different approaches should be used to treat different traits even in the absence of a full definition of MetSyn.…”
Section: Discussionmentioning
confidence: 99%